Microbial load and safety of paper currencies from some food vendors in Jimma Town, Southwest Ethiopia - Girma, Gosa (BMC Res Notes, 2014)
BACKGROUND: Paper currency is used for every type of commerce and plays an important role in the life of human beings. However, the combination of its widespread use and constant exchange make paper currency a likely agent for disease transmission. Thus, the aim of this study was to evaluate the microbial load and safety of Ethiopian paper currencies collected from some food vendors in Jimma town. METHODS: Standard microbiological methods were used for the enumeration of various microbial groups, isolation and characterization of pathogenic bacteria and their growth potential in selected weaning foods. A total of 100 samples of Ethiopian paper currencies, consisting of five denominations, from street food venders, hotels and cafeterias in Jimma town were collected aseptically. Sterile cotton swabs moistened with buffered peptone water solution were used for swabbing and the swabs were separately soaked into 10 ml sterile buffered peptone water solution. RESULTS: Mean microbial counts of Aerobic mesophilic bacteria, Staphylococci, Enterobacteriaceae, coliforms and Aerobic bacterial spores were (log CFU/cm(2)) 6.32, 4.43, 3.14, 2.98 and 3.78, respectively. However, mean counts of Yeasts and Moulds were below detectable levels. There was statistically significant variation (p < 0.05) among the mean counts of microbes isolated from samples of paper currencies. The predominantly isolated microbial groups were Staphylococcus spp. (34.06%) followed by Bacillus spp. (31.88%), Enterobacteraceae (13.39%), Micrococcus spp. (9.55%) and Streptococcus spp. (9.03%). Overall, 25% and 10% of the samples were positive for S. aureus and Salmonella spp, respectively. In challenge study, Salmonella spp. and S. aureus reached the infective dose within 12 to 18 hours of inoculation. CONCLUSION: Thus, paper currencies could be considered as one of the possible vehicles for transmission of disease causing microorganisms. Poor handling practices and personal hygiene of the food vendors could contribute to the observed microbial counts. Thus, it calls for awareness development on the potential risks associated with poor handling of paper currencies at all level of the food establishments.